Concurrent genetic and standard screening test for hearing reduction - Davcheva Chakar, Marina; Bozhinovski, Gjorgji; Shukarova Stefanovska, Emilija; Trajkov, Dejan (Macedonian Pharmaceutical Association, 2020)
Reduction of hearing is the most common sensory impairment among newborns with an incidence of 1-3 per 1000 births. Introduction of an Auditory Newborn screening program allows early identification of hearing impairment. Mainly, congenital hearing loss in early childhood is a result of genetic changes. Due to high frequency of GJB2 pathogenic variants, its molecular characterization among sensorineural hearing reduction cases is already conducted as a routine analysis in many countries. The aim of this study is to show our initial results in the effort to determine whether genetic screening along with the standard hearing screening in newborns is justified. Otoacoustic emission (OAE) method was conducted in 223 newborns at risk of hearing impairment. Among them, 7 did not pass the test in both ears while 9 exhibited one-sided hearing loss. In all 7 children with indication of profound bilateral deafness, the diagnosis was confirmed using auditory brainstem response. Genetic screening of GJB2 gene was performed in 6 of them. Genetic analysis of GJB2 revealed homozygous state of the most common pathogenic variant 35delG in 3 (50%) of the analyzed infants. In the remaining 3 no pathogenic variant was determined. The results indicate that performing auditory OAE together with genetic screening is justified. In newborns who have not passed the hearing screening test and have profound hearing loss, without other syndrome traits, screening for mutations of GJB2 gene should be conducted. Genetic screening enables establishment of early definite diagnosis for deafness and helps in conducting adequate therapy providing timely rehabilitation and social inclusion of deaf child.
Keywords: hearing loss; genetic screening; auditory screening; GJB2 gene